Biocompatible crosslinked β-cyclodextrin nanoparticles as multifunctional carriers for cellular delivery. Issue 34 (21st August 2018) - Datz, Stefan; Illes, Bernhard; Gößl, Dorothée; Schirnding, Constantin v.; Engelke, Hanna; Bein, Thomas
Abstract : Crosslinked β-cyclodextrin nanoparticles were synthesized to yield biocompatible nanocarriers that deliver hydrophobic drugs via sugar-mediated uptake into cells. Abstract : Nanoparticle-based biomedicine has received enormous attention for theranostic applications, as these systems are expected to overcome several drawbacks of conventional therapy. Herein, effective and controlled drug delivery systems with on-demand release abilities and biocompatible properties are used as a versatile and powerful class of nanocarriers. We report the synthesis of a novel biocompatible and multifunctional material, entirely consisting of covalently crosslinked organic molecules. Specifically, β-cyclodextrin (CD) precursors were crosslinked with rigid organic linker molecules to obtain small (∼150 nm), thermally stable and highly water-dispersible nanoparticles with an accessible pore system containing β-CD rings. The nanoparticles can be covalently labeled with dye molecules to allow effective tracking in in vitro cell experiments. Rapid sugar-mediated cell-uptake kinetics were observed with HeLa cells, revealing exceptional particle uptake within only 30 minutes. Additionally, the particles could be loaded with different cargo molecules showing pH-responsive release behavior. Successful nuclei staining with Hoechst 33342 dye and effective cell killing with doxorubicin cargo molecules were demonstrated in live-cell experiments, respectively. This novel nanocarrier concept provides a promising platform for the development of controllable and highly biocompatible theranostic systems.